Quantifying Wind Erosion During the Late Quaternary in the Qaidam Basin, Central Asia. Issue 12 (19th June 2019) - Wu, Lei; Prush, Veronica; Lin, Xiubin; Xiao, Ancheng; Zhang, Li; Chen, Ninghua; Yang, Rong; Chen, Hanlin
Abstract: Wind erosion is an important surface process on terrestrial planets but is difficult to quantify particularly on long‐term timescales. Here we use high‐resolution Terrestrial Laser Scanning and cosmogenic Beryllium‐10 ( 10 Be) exposure dating to investigate the yardangs, a wind‐eroded landform with aerodynamic forms, within the western Qaidam Basin, Central Asia. The results indicate that the yardangs started to form at ~105 ka, coincident with the early phase of the arid last glacial period. We further calibrated the wind erosion rate in the last glacial period to be ~0.26 mm/a, twice as fast as that of the present‐day interglacial period in our study site. Our results highlight the severe wind erosion during glacial periods and emphasize the fundamental control of global glacial‐interglacial climate oscillations on the secular variation in wind erosion in the Qaidam Basin during the late Quaternary period. Plain Language Summary: Wind prevails in arid to semiarid regions on the Earth and other terrestrial planets (e.g., Mars), forming distinctive landforms such as yardangs, sand dunes, and pans. It removes surficial rocks and soils over large areas and transports them tens to thousands of kilometers away before final deposition on land or in the ocean. Despite its importance as a facilitator of mass transport on the surface, we know little about how and when the wind erosion operates on the Earth and its relationship with global climate change. Through a detailed study of yardangs in the Qaidam Basin, one of the driest deserts in Central Asia, we determined that (1) the wind erosion that shaped the modern yardangs initiated in the early phase of the last glacial period (~105 ka) in the Qaidam Basin and (2) wind erosion during the last glacial period was twice as fast as that in the present‐day interglacial period in our study site, providing the first quantitative evaluation of the severe wind erosion during the cold and dry glacial periods of the Quaternary. Our findings yield meaningful insights in the link between climate change and aeolian processes. Key Points: We investigated yardangs in the Qaidam Basin using high‐resolution Terrestrial Laser Scanning and cosmogenic 10 Be exposure dating Modern yardangs formed since ~105 ka, in the early phase of the cold and arid last glacial period that facilitated intense wind erosion Wind erosion rates during the last glacial period were twice as fast as that of the present‐day interglacial period in the study site